Opertaional Tolerance in a Living Related Donor: A Case Report - Basit, Bilal; Sabir, Omer; Khalid, MOMINA (Pakistan Journal of Kidney Diseases, 2023)
Kidney transplant is the preferred treatment modality for end stage kidney disease (ESKD) patients. Ability to control immune response in the recipient by using lifelong immunosuppression leads to preservation of graft and immune tolerance2. Patients with kidney transplant require lifelong immunosuppression to prevent acute rejection. Rarely patients other than fraternal twins, may not require immunosuppression at all and such state is called operational tolerance. Few case reports have been reported in the literature of operational transplant and here we present the first case reported from Pakistan of operational transplant in a female who received kidney transplant donated by her younger sister.